A Humanized Diet Profile May Facilitate Colonization and Immune Stimulation in Human Microbiota-Colonized Mice - Moreno-Indias, Isabel; Lundberg, Randi; Krych, Lukasz; Metzdorff, Stine Broeng; Kot, Witold; Sørensen, Dorte Bratbo; Nielsen, Dennis Sandris; Hansen, Camilla Hartmann Friis; Hansen, Axel K. (Frontiers in Microbiology, 2020)
Background: In spite of the importance of the use of gnotobiotic mice for human fecal transfer, colonization efficiency and immune stimulation after human microbiota inoculation in mice are poorly studied compared to mouse microbiota inoculation. We tested the colonization efficiency and immune responses in mice bred for one additional generation after inoculating the parent generation with either a human (HM) or a mouse microbiota (MM). Furthermore, we tested if colonization efficiency and immune stimulation could be improved in HM-colonized mice by dietary approaches: if these were fed a diet closer to the human diet either in its sources of animal fat and protein (the ‘animal source’ (AS) diet) or in its proportions of macronutrients from the normal sources of a mouse diet (the ‘human profile’ (HP) diet). Results: Although significantly lower in mice with a human microbiota (30-40 % versus 61-70 %) the colonization efficiency was significantly higher in HM mice fed the HP diet (40 %), and in MM mice fed AS (70 %). The microbiota of mice fed HP was comparable to the microbiota of mice fed a standard rodent chow, while the microbiota of mice fed the animal source diet clustered separately. Mice inoculated with mouse fecal matter had significantly more CD4+ T cells and Cd4 expression and significantly fewer regulatory T cells and FoxP3 expression than human microbiota inoculated mice, but cell proportions differences were mostly apparent between mice fed the AS diet. Mice fed the HP diet had significantly higher expression of Cd8a. Conclusions: It is concluded that a diet with a humanized profile could support the establishment of a human microbiota in mice, which will, however, still elicit a lower colonization efficiency compared to mice inoculated with a mouse microbiota.